(untitled) (Ameghiniana, 2009)
The paleoenvironmental evolution of Laguna de Chascomús during the last 500 years is reconstructed based on ostracod assemblages and sedimentological and geochemical analyses from sediment cores. The chronology is constrained by one AMS 14C date on terrestrial material. The main hydrological and ecological characteristics of the lake are climatically- controlled. Three main expansion - contraction lake cycles have occurred during the last 500 years under different hydrological conditions. During periods of relatively higher water availability (end of 15th century - mid 17th century) lake waters were ß-oligohaline and HCO3- dominated; Limnocythere aff. L. sp. staplini was the dominant ostracod species and biodiversity was moderate. During periods of lower water availability (beginning of 18th century till mid 19th century, including the Little Ice Age), lake waters were ?-oligo to mesohaline, with higher salinities and Cl->HCO3-. Cyprideis hartmanni was dominant, and the ostracod assemblages have lower diversity. The paleohydrological evolution is compared to the available historical documents. A hydro-ecological conceptual model based on hydrochemistry, hydrology and ostracod assemblages is proposed to explain the evolution of the lake.